2009
DOI: 10.1108/10569210910987967
|View full text |Cite
|
Sign up to set email alerts
|

Organizational structure, support mechanism, and commercialization performance

Abstract: PurposeThe purpose of this paper is to investigate the influence of organizational structure (OS) of innovation teams and the external support mechanism on the commercialization of a small‐ and medium‐sized new venture.Design/methodology/approachTaking the perspective of inter‐organizational cooperation, this paper tries to adopt complementary view of transaction cost economics and resource dependency theory and employ enterprises in incubation centers in Taiwan as the empirical subjects. More specifically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, regarding internationalization processes an empirical research developed in Hungary found that not only organizational mechanisms (e.g. participation of the foreign parent or focusing on a concrete kind of information) affect the performance of an international joint venture, but also organizational characteristics of the firms have a strong influence (Alharbi et al, 2016;Chiu and Chang, 2009;Lyles and Salk, 2007).…”
Section: Organizational Mechanismsmentioning
confidence: 99%
“…However, regarding internationalization processes an empirical research developed in Hungary found that not only organizational mechanisms (e.g. participation of the foreign parent or focusing on a concrete kind of information) affect the performance of an international joint venture, but also organizational characteristics of the firms have a strong influence (Alharbi et al, 2016;Chiu and Chang, 2009;Lyles and Salk, 2007).…”
Section: Organizational Mechanismsmentioning
confidence: 99%
“…The second stream is that of "institutional and organizational resources". This was proposed at the beginning of the 21 st century and indicates favorable institutional and organizational resources include supportive commercial infrastructures, organizational motivations, having access to risky capital and investment and plays a major role in enhancement of commercial performance of research (Chang et al, 2009). Given to the limited volume of paper, effective factors on knowledge commercialization are summarized in table (2) that have been presented by researchers and research institutions.…”
Section: -2 Research Backgroundmentioning
confidence: 99%
“…3 Commercialization of researches is a process that converts the produced knowledge in research organizations into suppliable products in the market or industrial processes (Salter & Martin, 2001). 4 Commercialization is the process of developing a business through feasibility study of an idea and applying it until its acceptance in the market (Rosa & Rose, 2007).…”
Section: -Literature Review and Research Background 2-1 Definition Omentioning
confidence: 99%
“…While formalization refers to written job descriptions, also policies and procedures that guide the actions of employees in an organization, specialization refers to the willingness and ability to transfer employees among different departments within an organization and centralization refers to the centrality of location of decision-making. Elsewhere, specialization refers to specialized skills of personnel in the entire functional areas firm (Chiu and Chang, 2009). Respondents were asked to indicate the intensity of formalization and centralization in their firms on a five-point Likert scale ranging from (1) "not at all" to (5) ".…”
Section: Measurement Of Variablesmentioning
confidence: 99%